RP-HPLC method development and validation for bedaquiline fumarate to evaluate its forced degradation behaviour and stability in official dissolution media - Vishwas Pardhi; Geetanjali Pant; S. J. S. Flora (Future Journal of Pharmaceutical Sciences, 2020)
Abstract Background A simple, rapid and accurate reverse phase RP-HPLC method for the validation of antitubercular drug bedaquiline fumarate (BQF) was developed. The stability and forced degradation behaviour of bedaquiline fumarate (BQF) in official dissolution media (0.01 N HCl) and methanol were assessed. Results The method provided linear responses within the concentration range which varies from 10 to 100 μg/mL with LOD values of 2.6 μg/mL and LOQ of 7.9 μg/mL. Mean percent recovery varied between 97.46 and 103.82% and precise mean RSD of 0.31% (repeatability) and 0.48% (intermediate precision). The method was validated for other parameters like specificity, system suitability and robustness. Potential degradation of the BQF when exposed to direct sunlight in official dissolution media was 90.75% and in methanolic stock solution was 91.98%. Acid-alkali degradation study showed 86.59% loss of BQF in 0.5 N NaOH, and in acidic environment (0.5 N HCl), there was 6.15% loss. Thermal degradation of BQF was 70.11% loss in official dissolution media at 80 °C. No significant change in drug concentrations was noted when exposed and protected from normal daylight at room temperature and at 2–8 °C temperature. Conclusion The developed method has significant applicability for the qualitative and quantitative determination of BQF in different pharmaceutical formulations in the official dissolution media in routine quality control analysis.